Karakteristik dan Perilaku Kewirausahaan Petani Lada Putih Muntok - Rufti Puji Astuti; Novyandra Ilham Bahtera; Eddy Jajang Jaya Atmaja (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
Entrepreneurship is one of the human capital variables of pepper farmers that plays an important role in determining the success of pepper agribusiness development in this creative era. To face the challenges of the business climate change, pepper farmers need entrepreneurship. The objectives compiled in this study are to identify the entrepreneurial characteristics of Muntok White Pepper farmers and to analyze the effect of entrepreneurial characteristics on their entrepreneurial behavior in managing to farm. The study was conducted by survey method, involving 115 farmers. Data analysis used Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results showed that the entrepreneurial characteristics of pepper farmers are risk-taking, responsive to opportunities, innovative, and motivated. Also, the results showed that the entrepreneurial characteristics of pepper farmers positively and significantly influence their entrepreneurial behavior. Furthermore, the most dominant variable reflecting their entrepreneurial characteristics is the courage to take risks. This study recommends muntok pepper farmers that they always dare to take risks, be persistent and disciplined. Additionally, knowledge and skills need to be constantly updated to grow the ability to innovate and be creative in carrying pepper cultivation activities out.